Examination results of medical students with dyslexia. - McKendree, J; Snowling, M (2011)
CONTEXT: dyslexia is a learning disorder, the primary sign of which is significant difficulty in learning to read and spell. However, accumulating evidence suggests that many people with dyslexia can overcome their reading difficulties and enjoy high levels of educational success. There is debate about the appropriateness of different forms of summative assessment for people with dyslexia, but there is little research investigating different examination formats, particularly in higher education, including medical education. Currently, medical school examinations comprise a range of different assessments, both written and performance-based, offering an opportunity to compare performance on different formats. This study compared results between students with and without dyslexia on all summative assessment types used at one UK medical school. METHODS: examination scores were collated for all summative Year 1 and 2 examinations at Hull York Medical School (HYMS) over four cohorts entering from 2004 to 2007. These included scores on two types of forced-choice question (multiple-choice and extended matching question) examinations, on short written answer examinations and on performance in a 16-station objective structured clinical examination (OSCE). Results for written answers were gathered separately for basic science questions and for questions involving critical analysis and evidence-based medicine. RESULTS: an overall multivariate analysis of covariance (mancova) on examinations across both years controlling for gender, ethnicity and age on entry indicated that there was no significant overall effect of dyslexia on examination results. Regression analysis further showed that dyslexia was not a significant predictor on any of the examination forms in Year 1 or Year 2. CONCLUSIONS: there is no indication that any of the assessment methods used in HYMS, in common with many other medical schools, disadvantage students with dyslexia in comparison with their peers. In the light of these findings, we support the current view that a variety of assessment types should be included in the assessment of all medical students, as is already considered to be best practice.